Pengaruh Rasio Beban dan Pendapatan Operasional, Nonperforming Loan, Loan To Deposit Pada Pertumbuhan Profitabilitas - Suputra, Krisna Ekayana; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p14, 2017)
ABSTRACT LPD's profit growth reflects the improvement of LPD's financial performance and high public trust and community satisfaction. In an effort to improve this performance, LPD is required to improve its health analysis. Health analysis proxyed with CAR, KAP, PPAP, BOPO, ROA, LACLR and LDR are closely related to profit growth. This study aims to test empirically the influence of CAR, KAP, PPAP, BOPO, ROA, LACLR and LDR to profit growth. Profitability shows how efficiently an LPD or financial institution has operated. There are several things that affect the development of LPD profitability such as capital adequacy, credit problems and funds from third parties. There are several ratios that can be used to measure how capital adequacy, credit problems and third-party funds can affect the profitability of an LPD. The ratios are, among others, capital adequacy ratio, non performing loan and loan to deposit ratio. This study aims to obtain empirical evidence Influence Operating Ratios Operating Ratio, Non Performing Loan and Loan to Deposit Ratio on Profitability Growth. Empirical study was conducted at Lembaga Perkreditan Desa (LPD) in Badung Regency period 2013 - 2015. Population used in this research is all LPD in Badung regency which report annual financial report to LPLPD of Badung Regency period 2013-2015 with simple random sampling method. Based on the method of determining the sample obtained sample of 54 LPD. Data analysis technique used multiple linear regression analysis. The results showed that the loan to deposit ratio has a positive effect on the growth of profitability. Operating expenses for operating income and non-performing loans did not affect profitability growth. Keywords: Operating Income Operating Expenses, Non Performing Loans, Loan to Deposit Ratio and Profitability Growth.